2015
DOI: 10.1262/jrd.2014-139
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid binding protein 6 gene (<i>Fabp6</i>) is expressed in murine granulosa cells and is involved in ovulatory response to superstimulation

Abstract: The fatty acid binding protein 6 (Fabp6) is commonly regarded as a bile acid binding protein found in the distal portion of the small intestine and has been shown to be important in maintaining bile acid homeostasis. Previous studies have also reported the presence of Fabp6 in human, rat and fish ovaries, but the significance of Fabp6 in this organ is largely unknown. Therefore, we surveyed murine ovaries for Fabp6 gene expression and evaluated its role in ovarian function using mice with whole body Fabp6 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Although the function of FABP6 is not fully elucidated, even in enterohepatic tissues, it may be possible that FABP6 has a role in transcellular shuttling of sex hormones in the ovary, as previous studies have demonstrated that FABP6 is involved in intracellular transport of bile acids in enterocytes [14, 37, 38]. In FABP6-deficient mice [39], the ovulation rate after superovulatory treatment was markedly decreased compared to that in wild-type mice, which suggests that FABP6 is involved in fertility via a function in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of FABP6 is not fully elucidated, even in enterohepatic tissues, it may be possible that FABP6 has a role in transcellular shuttling of sex hormones in the ovary, as previous studies have demonstrated that FABP6 is involved in intracellular transport of bile acids in enterocytes [14, 37, 38]. In FABP6-deficient mice [39], the ovulation rate after superovulatory treatment was markedly decreased compared to that in wild-type mice, which suggests that FABP6 is involved in fertility via a function in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of FABPs is to bind and transport fatty acids within cells with variable selectivity, a nities, and binding mechanisms [27,40]. Consequently, different FABP members [41][42][43][44][45][46][47][48] have a crucial role in lipid and energy metabolism of the entire body by regulating FA tra c in the cytoplasmic and nuclear compartments of different cell kinds. Studies with various transfected cell types overexpressing FABPs and with different cultured primary cell types from FABP knockout mice showed that FABPs enhance FAs uptake and incorporation into triglycerides and phospholipids.…”
Section: Inhibition Of Fabp3 In Insulin-secreting Islet Cells May Pro...mentioning
confidence: 99%
“…26 Some types have widespread tissue distribution while others are restricted to one or a few tissues (Table S1). Selected examples include Fabp5 which appears to be the most widely distributed paralog of the Fabps in humans (Table S1), Fabp6 which resides in intestinal and ovarian tissues 27…”
Section: Iscovery Of Fab Psmentioning
confidence: 99%